Visionary Leadership Strategies to Enhance Organizational Innovation and Sustainability - Djawas, Fathia Wardah S; Hidayatullah, Cahyo; Abdussyukur, Mohammad Azmi; Dinata, Rian Fauza; Rifai, Akbar Syahbana (Review: Journal of Multidisciplinary in Social Sciences, 2025)
In the era of globalization and rapid technological development, organizations are required to continuously innovate and maintain their operational sustainability. Visionary leadership presents a strategic approach that can answer these challenges by emphasizing long-term vision, empowering human resources, and creating a work culture that supports innovation. This study aims to explore the strategy of visionary leadership in driving organizational innovation and sustainability through a Systematic Literature Review (SLR) approach. The results of the study indicate that visionary leaders have a crucial role in creating a collaborative, adaptive work environment, and are able to connect strategic vision with concrete operational implementation. Furthermore, visionary leadership has proven relevant and effective not only in the private sector, but also in the public sector. With its ability to inspire and direct organizations towards a competitive future, visionary leadership is an important foundation in building competitive and sustainable organizations.